Nano-Silica modifier asphalt concrete under rutting resistance and shape memory component - Putra Jaya, Ramadhansyah; A. A., Mohammed; Mwangi, P. M.; M. P., Anwar; Leong, Lau Teck; Jayaprakash, Jaganathan; Z. F., Mohamed Jaafar; Mashros, N. (IOP Publishing Ltd, 2021)
Permanent deformation is pavement distress that has been the root cause of failure of roads globally. With the formation of a rut, follows cracking which inevitably damages the asphalt and sub-base layers. To curb the rutting distress, this study investigates the use of nanosilica, miniaturized silica particles to the power of 10-9 to modify the binder of the asphalt concrete. The nano-silica was added at 4%, 6% and 15% by weight of bitumen into the asphalt mixture. Marshall Mix design method was used to prepare the forty-eight samples used in the study. Repeated Load Permanent Deformation (RLPD) test and Shape Memory (SM) were performed at two temperatures (25°C and 40°C). It was found that the rutting resistance and shape memory had the best performance with the addition of 15% nano-silica at 40°C. Addition of nano-silica at 15% by weight of bitumen had the best amelioration of not only permanent deformation resistance but also shape retention thus enhancing pavement performance.